The challenges of climate change and human impacts faced by Mexican coasts: A comprehensive evaluation - María Luisa Martínez; Rodolfo Silva; Valeria Chávez; Jorge López-Portillo; Karla Salgado; Etzaguery Marín-Coria; Octavio Pérez-Maqueo; Carmelo Maximiliano-Cordova; Rosario Landgrave; Víctor de la Cruz (PLoS ONE, 2025)
The extensive shoreline of Mexico is heterogeneous and diverse, but it is increasingly exposed to degradation and loss. This is the first study performed at a national level and with a multidisciplinary approach, that aims to assess the impact of climate change and human-related pressures affecting Mexican coasts. From 1863 to 2022, 386 tropical cyclones have landed on Mexican coasts, six of them of category 5 (most on the Atlantic). Sea level rise projections showed that the Atlantic coast is the most vulnerable, whereas intense coastal erosion ( > 25m/year) is more widespread on the northern Pacific coast. Human impacts include coastal urbanization, ecosystem degradation and coastal armouring. Six million people live on Mexican coasts, mostly in the Caribbean. Mangroves and coastal dunes each cover nearly 800,000 ha. The mangroves are relatively well preserved, but almost half the area of the coastal dunes is degraded. Coastal armouring is widespread along the coasts, but most of these structures (55%) are found on the Yucatan peninsula. Activities required to improve the condition of Mexican coasts and make them a sustainable place to live would include: adaptation of human settlements to the conditions of the dynamic coasts; appropriate coastal protection measures that do not induce downdrift erosion; dealing with coastal risks by restoring and preserving coastal ecosystems.